Technological Innovation, Public Trust, and Policy Strategies For A Sustainable Financial Sector: A Systematic Review - Eristian Wibisono; Mochammad Nurul (National Research and Innovation Agency, Indonesia, 2025)
This study aims to address a gap in the literature exploring the state of innovation in the financial industry by presenting key findings and insights from such research. Specifically, it addresses research questions related to the experiences and determinants of successful implementation of financial innovation in different countries, the underlying challenges that often arise, and solutions to overcome them. A systematic literature review (SLR) method was used to explore and investigate the research problem by applying three main protocols: scoping the literature, selecting and retrieving the most relevant articles, and critically reviewing the selected articles. The results of the current study indicate that studies related to financial innovation have grown significantly and are published in medium to high-quality literature sources, but much effort is still needed to bring this topic to a more mature stage. A critical review of previous research results in three main propositions contributing to this study. These include factors that facilitate successful financial innovation, overcoming challenges related to public trust, and policy strategies for sustainable financial innovation.